Exploring the challenges facing micro enterprise immigrant traders in the Western Cape metropole : Greenmarket Square and the Hout Bay Harbour markets - Chikamhi, Tendai (Department of Social Development, 2014)
This study explored the challenges facing immigrant traders in the Western Cape Metropole at the Greenmarket Square and the Hout Bay Harbour markets. A purposive / convenience sample was drawn of twelve immigrant traders and five key informants (seventeen participants). An exploratory, qualitative approach was adopted using semi-structured interview schedules to guide face to face interviewing. The data was analysed using Tesch's (1990) approach.